2005
DOI: 10.1124/jpet.105.094656
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nitric-Oxide Synthase Inhibition Facilitates Adrenergic Neurotransmission in Rat Mesenteric Resistance Arteries

Abstract: The effects of nonselective nitric-oxide synthase (NOS) inhibitors [N--nitro-L-arginine methyl ester (L-NAME) and N--nitro-L-arginine (L-NNA)] and specific neuronal NOS (nNOSon adrenergic nerve-mediated vasoconstriction were studied in rat perfused mesenteric vascular beds without endothelium. Perfusion of L-NAME, L-NNA, or L-VNIO markedly augmented vasoconstrictor responses to periarterial nerve stimulation (PNS; 2-8 Hz) without affecting vasoconstriction induced by exogenously injected norepinephrine (NE). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 27 publications
(29 reference statements)
4
52
2
Order By: Relevance
“…In circuits of larger animal species, NO derived from nNOS has been suggested to act either as a co-transmitter with CGRP or as a single neuromodulator released from nitrergic nerve terminals, as recently revisited by Hatanaka et al (2006). Assuming that in our model, 7-NI selectively inhibits the neuronal isoform, our results would support an important role for nNOS as a pre-junctional modulator of the CGRPreleasing nerve terminals since the inhibitor potentiated the response to NANC stimulation.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In circuits of larger animal species, NO derived from nNOS has been suggested to act either as a co-transmitter with CGRP or as a single neuromodulator released from nitrergic nerve terminals, as recently revisited by Hatanaka et al (2006). Assuming that in our model, 7-NI selectively inhibits the neuronal isoform, our results would support an important role for nNOS as a pre-junctional modulator of the CGRPreleasing nerve terminals since the inhibitor potentiated the response to NANC stimulation.…”
Section: Discussionsupporting
confidence: 51%
“…It is noteworthy that Ralevic (2002) showed that the release of transmural NO represses NANC-dependent vasodilatation, albeit the specific contribution of the neuronal isoform was not identified. In addition, Hatanaka et al (2006) have recently reported that nNOS is a potent repressor of adrenergic-dependent vasoconstriction following perivascular nerve stimulation of the rat arterial mesenteric bed. Therefore, nNOS may significantly depress the overall (that is autonomic and C-fibre-dependent) perivascular nervous control of mesenteric tone in the mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Thus, perivascular NO-containing nerves (nitrergic nerves) have been shown to distribute in various blood vessels as nonadrenergic noncholinergic nerves. [5][6][7] In addition to NO's direct vasodilator effect, it has also been shown to modulate adrenergic neurotransmission. 8,9 Our previous study showed that NO, which is released from nitrergic nerves, presynaptically inhibits neurogenic noradrenaline release to modulate adrenergic neurotransmission in rat mesenteric arteries without an endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Our previous study showed that NO, which is released from nitrergic nerves, presynaptically inhibits neurogenic noradrenaline release to modulate adrenergic neurotransmission in rat mesenteric arteries without an endothelium. 6 Furthermore, several studies have shown that inhibition of NO synthesis results in augmented adrenergic nerve-mediated vasoconstriction in the rat tail artery, 10 the large coronary artery of anesthetized dogs 11 and the isolated adrenal medulla vessels of dogs. 8 These findings imply that NO has a role in the modulation of adrenergic neurotransmission.…”
Section: Introductionmentioning
confidence: 99%